2019
DOI: 10.1111/ijcp.13334
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of topical gentamycin application on prophylaxis and treatment of wound infection: A systematic review and meta‐analysis

Abstract: Summary Objectives The purpose of this study was to conduct a systematic review and meta‐analysis in patients with local wound infection or infective risk, evaluating effects of topical gentamycin application on prophylaxis and treatment of wound infection. Methods Embase, the Cochrane Library, Pubmed, Medline (from Ovid) and three Chinese literature databases (CNKI, VIP and WANFANG) were searched. Randomised controlled studies (RCTs) and observational studies (OSs) that assessed the efficacy of topical gentam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that P. aeruginosa -produced HQNO increases the tolerance of S. aureus to aminoglycosides in vitro ( 45 ); thus, we focused on this phenotype. We tested two different aminoglycosides: gentamicin, which has been used to successfully treat wound infections ( 49 , 50 ), and tobramycin, which is commonly used to treat chronic lung infections and more recently has been pursued as a prophylactic treatment to prevent wound infections ( 51 , 52 ). We first tested if S. aureus had altered tolerance in coinfected wounds and the role that HQNO plays in aminoglycoside tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that P. aeruginosa -produced HQNO increases the tolerance of S. aureus to aminoglycosides in vitro ( 45 ); thus, we focused on this phenotype. We tested two different aminoglycosides: gentamicin, which has been used to successfully treat wound infections ( 49 , 50 ), and tobramycin, which is commonly used to treat chronic lung infections and more recently has been pursued as a prophylactic treatment to prevent wound infections ( 51 , 52 ). We first tested if S. aureus had altered tolerance in coinfected wounds and the role that HQNO plays in aminoglycoside tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…Gentamicin (GEN) is an aminoglycoside antibiotic that can be used for topical application to treat chronic wounds [ 12 ]. Recent clinical studies reveal that topical GEN application reduces the duration of wound healing [ 13 ], however, treatments should be limited in duration due to concerns about antibiotic resistance [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The gentamicin sulfate cream was chosen as the topical antibiotic for this study because it is an FDA‐approved broad‐spectrum antibiotic that is commonly used to prevent and treat a wide variety of bacterial infections. A recent systematic review, meta‐analysis found that topical gentamicin cream application for wound infection prophylaxis and treatment significantly increased clinical efficacy and decreased the duration of wound healing 21 . In addition, we have previously demonstrated both in preclinical models as well as in clinical case studies that topical application of gentamicin with the PWD is efficient and safe 6 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review, meta‐analysis found that topical gentamicin cream application for wound infection prophylaxis and treatment significantly increased clinical efficacy and decreased the duration of wound healing. 21 In addition, we have previously demonstrated both in preclinical models as well as in clinical case studies that topical application of gentamicin with the PWD is efficient and safe. 6 In a porcine study, ultrahigh concentrations (1000×MIC) of gentamicin delivered via PWD were used to treat P. aeruginosa ‐infected deep partial‐thickness burn wounds.…”
Section: Discussionmentioning
confidence: 99%